Determinasi Pengambilan Keputusan Memilih Program Studi Pendidikan Akuntansi: Peran Moderasi Prospek Kerja - Atifatul Alifah; Ahmad Nurkhin (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2025)
This study aims to analyze the influence of parental support, education costs, and the reputation of the study program on student decision-making in choosing the Accounting Education study program at Universitas Negeri Semarang with job prospects as a moderating variable. This research uses a quantitative approach with population in this study of 167 students of Accounting Education, Universitas Negeri Semarang, class of 2023. The sampling technique used is the probability sampling technique with proportional random sampling which resulted in a sample of 118 students. The data analysis technique in this study used descriptive statistical analysis and moderated regression analysis/MRA (Moderated Regression Analysis) with the help of SPSS 25. The results of the study show that parental support, education costs, and the reputation of the study program have a positive and significant effect on students' decision making in choosing a study program. Job prospects are unable to strengthen the influence of parental support, education costs, and the reputation of the study program on students' decision making in choosing a study program.